Analogue modelling of different angle thrust-wrench fault interference in a brittle medium. (May 2015) - Rosas, F.M.; Duarte, J.C.; Schellart, W.P.; Tomás, R.; Grigorova, V.; Terrinha, P.
Abstract: Analogue modelling experiments of thrust-wrench fault interference in a brittle medium are presented and discussed. Simultaneous reactivation of confining strike-slip and thrust faults bounding a (corner) zone of interference defined by the angle between the two fault systems is simulated, instead of previously reported discrete (time and space) superposition of alternating thrust and strike-slip events. The influence of different considered interference angles of 60°, 90° and 120° is investigated through comparison between the obtained structural configurations in each case. It is shown that under these conditions a characteristic morpho-structural pattern with a deltoid shape resembling a tie-knot consistently forms in the (corner) zone between the two fault systems. The specific structural configuration of a such tie-knot structure (TKS) varies significantly as a function of the prescribed fault interference angle, which determines the orientation of the displacement vector shear component ( d s → ) along the main frontal thrust system, and critically controls the geometry and kinematics of the TKS. Comparison with three natural examples shows remarkable geometric and kinematic similarity, confirming model predictions and suggesting the existence of common underlying dynamic processes governing the specific (TKS) structural configuration of different thrust-wrench fault interference corner-zones in nature. Highlights: Analogue modelling of simultaneous thrust-wrench fault interference. Newly recognized deltoid shaped (corner-zone) interference pattern: Tie-Knot Structure (TKS). Different TKS morphological and kinematical configuration as a function of differently considered fault interference angle. Recognition of geometrical and kinematical similitude with several natural case studies.